Alternative pathways to sustainable seafood. Issue 1 (4th November 2019) - Stoll, Joshua S.; Bailey, Megan; Jonell, Malin
Abstract: Seafood certifications are a prominent tool being used to encourage sustainability in marine fisheries worldwide. However, questions about their efficacy remain the subject of ongoing debate. A main criticism is that they are not well suited for small‐scale fisheries or those in developing nations. This represents a dilemma because a significant share of global fishing activity occurs in these sectors. To overcome this shortcoming and others, a range of "fixes" have been implemented, including reduced payment structures, development of fisheries improvement projects, and head‐start programs that prepare fisheries for certification. These adaptations have not fully solved incompatibilities, instead creating new challenges that have necessitated additional fixes. We argue that this dynamic is emblematic of a common tendency in natural resource management where particular tools and strategies are emphasized over the conservation outcomes they seek to achieve. This can lead to the creation of "hammers" in management and conservation. We use seafood certifications as an illustrative case to highlight the importance of diverse approaches to sustainability that do not require certification. Focusing on alternative models that address sustainability problems at the local level and increase fishers' adaptive capacity, social capital, and agency through "relational" supply chains may be a useful starting point.